2020
DOI: 10.3389/fpsyt.2020.00878
|View full text |Cite|
|
Sign up to set email alerts
|

The UK National Homicide Therapeutic Service: A Retrospective Naturalistic Study Among 929 Bereaved Individuals

Abstract: Homicidal bereavement puts survivors at risk of developing a broad range of lasting and severe mental health problems. Previous research has often relied on relatively small and homogenous samples. Still, little is known about what factors influence the expression of symptoms following homicidal bereavement. Preventive and curative treatments often do not consider the complex coherence between the emotional, judicial, financial, and societal challenges that likely arise following a homicide. Despite the severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…Does the loss also mean a loss of confidence in the legal system, the government or society? British data show that a slow trial or the absence of a judgement is accompanied by a slower recovery during specialized treatment of surviving relatives after murder (Soydas et al, 2020). Armed conflict situations are often characterized by the absence of a functioning juridical system, forcing people to migrate with the associated political, administrative and economic constraints alongside loss of culture and social support.…”
Section: Juridical and Political Situationmentioning
confidence: 99%
“…Does the loss also mean a loss of confidence in the legal system, the government or society? British data show that a slow trial or the absence of a judgement is accompanied by a slower recovery during specialized treatment of surviving relatives after murder (Soydas et al, 2020). Armed conflict situations are often characterized by the absence of a functioning juridical system, forcing people to migrate with the associated political, administrative and economic constraints alongside loss of culture and social support.…”
Section: Juridical and Political Situationmentioning
confidence: 99%
“…Studies focusing on the individual level noted the following HB risk factors: prior mental health or emotional fluctuation (Alves-Costa, Hamilton-Giachritsis, & Halligan, 2021; Soydas et al, 2020; Williams et al, 2012); immigration (Alisic, Groot, Snetselaar, Stroeken, & van de Putte, 2017); prior health or physical problems (Currier et al, 2015; Soydas et al, 2020; Williams et al, 2012); low socioeconomic status (Douglas et al, 2021); belonging to an ethnic or racial minority (Douglas et al, 2021; Kaplow et al, 2021; Kassing et al, 2021; Keesee et al, 2008; McDevitt-Murphy et al, 2012; Williams et al, 2012); prior victimization or stressful life events (Douglas et al, 2021; Kassing et al, 2021; Park & Benore, 2004; Soydas et al, 2021); female gender, with mothers and sisters grieving more intensely over time than fathers and brothers (Dyregrov et al, 2015; Kaplow et al, 2021; Kassing et al, 2021; Soydas et al, 2020, 2021); and being younger (Murphy, Johnson, Wu, et al, 2003; Pfeffer et al, 2007; Stanley et al, 2019). Additional HB risk factors noted as having more pathogenic effects include negative cognitions (Alves-Costa, Hamilton-Giachritsis, & Halligan, 2021; Bailey, Sharma, et al, 2013; Boelen et al, 2015), attachment anxiety and avoidance (Currier et al, 2015), a sense of social disconnection (Smith et al, 2020), lesser ability to construct meaning (Zakarian et al, 2019), and low level of spirituality and religiosity (Boulware & Bui, 2016; Burke et al, 2011; Currier et al, 2013; Johnson, 2021; Johnson & Zitzmann, 2020, 2021; Lee et al, 2020; Mastrocinque et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have indicated that a homicide’s characteristics have an influence on HB. The following homicide-related factors have been reported as HB risk factors: close familial relations with the victim (Alisic, 2018; Alves-Costa, Hamilton-Giachritsis, & Halligan, 2021; Johnsen & Dyregrov, 2016; Kaplow et al, 2021; Matthews & Marwit, 2004; Moss & Raz, 2001; Ogata et al, 2011; Soydas et al, 2020); close domestic relations with both the victim and killer (Alisic, 2018; Alisic, Groot, Snetselaar, Stroeken, & van de Putte, 2017; Clements & Burgess, 2002; Hardesty et al, 2008; Kapardis et al, 2017; Kaplan et al, 2001; Stanley et al, 2019; Steeves & Parker, 2007); continuing bonds with victim (Moss & Raz, 2001); the killer being the bereaved person’s parent (Kapardis et al, 2017); interfamilial homicide (Jackson et al, 2021); the victim and bereaved person belonging to a racial minority (Douglas et al, 2021; Kaplow et al, 2021; Kassing et al, 2021; McDevitt-Murphy et al, 2012; Williams et al, 2012); being the parent of a child who was killed at a young age (Matthews & Marwit, 2004; Murphy, Johnson, Chung, et al, 2003; Murphy, Johnson, Wu, et al, 2003; Nzewi et al, 2002); the homicide scene being the bereaved person’s home (Alisic, Groot, Snetselaar, Stroeken, et al, 2017; Alisic, Groot, Snetselaar, Stroeken, & van de Putte, 2017); children hearing or witnessing the killing (Clements & Burgess, 2002); the homicide resulting in multiple victims (Huggins & Hinkson, 2022; Kaplow et al, 2021; Lenferink, de Keijser, et al, 2017); the homicide being related to terror circumstances (Dyregrov et al, 2016; Johnsen & Dyregrov, 2016; Pfeffer et al, 2007); the killer’s criminal process resulting in acquittal (Thiel, 2016); and the killing being an unresolved homicide, known as a cold case (…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations